Prediction models for diagnosis and prognosis of covid-19 infection: systematic review and critical appraisal - Wynants, L; Van Calster, B; Bonten, MMJ; Collins, GS; Debray, TBA; De Vos, M; C Haller, M; Heinze, G; Moons, KGM; Riley, RD; Schuit, E; Smits, LJM; et al. (BMJ, 2020)
Objective: To review and critically appraise published and preprint reports of prediction models for diagnosing coronavirus disease 2019 (covid-19) in patients with suspected infection, for prognosis of patients with covid-19, and for detecting people in the general population at risk of being admitted to hospital for covid-19 pneumonia.